Differential auditory-oculomotor interactions in patients with right vs. left sided subjective tinnitus: a saccade study - Lang, Alexandre; Vernet, marine; Yang, Qing; Orssaud, Christophe; Londero, Alain; Kapoula, Zoi (Frontiers in Human Neuroscience, 2013)
Subjective tinnitus (ST) is a frequent but poorly understood medical condition. Recent studies demonstrated abnormalities in several types of eye movements (smooth pursuit, optokinetic nystagmus, fixation and vergence) in ST patients. The present study investigates horizontal and vertical saccades in patients with tinnitus lateralized predominantly to the left or to the right side. Compared to left sided ST, tinnitus perceived on the right side impaired almost all the parameters of saccades (latency, amplitude, velocity, etc.) and noticeably the upward saccades. Relative to controls, saccades from both groups were more dysmetric and were characterized by increased saccade disconjugacy (i.e. poor binocular coordination). Although the precise mechanisms linking ST and saccadic control remain unexplained, these data suggest that ST can lead to detrimental auditory, visuomotor and perhaps vestibular interactions.